A study on value added dairy products and availability of milk, meat and egg at consumers’ level in selected areas of Bangladesh - Uddin, MT; Islam, MM; Nasrin, M (Bangladesh Journal of Livestock Research, 2020)
The goal of the study was to analyze the different actors involved in the dairy products value chain with their value addition activities and estimate the demand for livestock products through measuring the availability of milk, meat and egg at individual level. With this goal, the study was conducted in four districts namely Sirajganj, Bogra, Rangpur and Narsingdi which were selected purposively for this study based on concentration of dairy farming and the presence of dairy processing plants/companies. The simple random sampling technique was followed to select a total of 240 from six types of stakeholders/ actors i.e., input suppliers, dairy farmers, milk traders, processing plants/companies including their branches/agents, credit organizations and service providers, and consumers of livestock products. Data and information were analyzed by using descriptive statistics, mathematical techniques, enterprise analysis, SWOT analysis and value chain analysis followed by graphical presentation. Cost of milk per litre was highest in Narsingdi (Tk. 25.33) and lowest in Sirajganj (Tk. 19.66). Dairy farmers in Narshingdi derived highest net return per cow per day (Tk. 109.48). Investment in dairy farming was highly profitable since BCR per day per cow in all the districts were more than one. Collection point/processing plants added highest value (35.5%) to a product followed by farmers (25.2%), milk traders (28.3%) and retailers (11.0%). The availability of milk, meat and egg was higher in all the study areas than the national average. The impact of price and income on quantity demand was statistically significant for all the products. The demand for milk and egg was price elastic whereas demand for meat was price inelastic. On the other hand, the demand for livestock products was found as income inelastic. However, in spite of various problems and threats, there is a great export potential for value added dairy products along with satisfying the unmet consumer demand in the domestic market for such products. Bangladesh J. of Livestock Res. 21-25: 45-55, 2018